IN VITRO STUDY OF THE EFFECT OF SOME PREPARED OXADIAZOLE DERIVATIVES ON ALP, AST AND ALT ACTIVITIES IN SERA OF HEPATOCELLULAR CANCER PATIENTS AND HEALTHY CONTROL - Samir, Ali H; Jawad, Alaa Hussein; Al-Rubaei, Zeinab M Malik (Al-Nahrain Journal of Science, 2018)
The effect of some prepared oxadiazole compounds 5-[4-(p-methoxy phenyl) azo phenyl]-2-thiol-1, 3, 4-Oxadiazole [ ], 5-[4-(methoxy phenyl) azo phenyl]-2-marcapto-alky-1, 3, 4-oxadiazole[ -V]( where alkyl group is ethyl, propyl, butyl and pentyl respectively) were tested on the activityof ALP, AST, and ALT in sera of 30 patients with hepatocellular cancer and 30 healthy individualsas control group.The results revealed significantly higher levels of ALP, AST, and ALT activity in patients groupcompared to control group.Different concentrations (10-4, 10-5, and 10-6M) of oxadiazole derivatives showed differentpercentage of inhibitions, but did not showed proportional with the concentration of derivatives.The elevated values of ALP, AST, and ALT activity in sera of patients were returned to aboutnormal values in most cases after addition of oxadiazole compounds to sera of patients in vitro.